Development of Budesonide Oral Colon Specific Drug Delivery System using Interpolymer Complexation Method - Ramgonda, Patil; Masareddy, Rajashree Shashidhar; Patil, Archana; Bolmal, Uday (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Oral bioavailability of Budesonide is 10% due to its extensive first pass metabolism, its high volume of distribution and 85-90% of protein binding. Protection of drug release in stomach and targeting drug to colon which is an absorption site of drug is an attempt to improve therapeutic efficacy. The objective of this study was to develop interpolymer complex microspheres of Budesonide for oral colon specific drug delivery. Methods: Emulsion solvent evaporation method was used in the preparation of microspheres. Microspheres prepared at different polymer ratio and surfactant concentration were analysed for its mean particle size, surface morphology, flow property, drug release, % encapsulation efficiency. Results: Microspheres prepared with 3:5 polymer ratios F4 was optimized with respect to its % EE, in vitro drug release and percentage yield. Drug release from formulated tablets containing microspheres of 3:5 polymer ratios showed an extended release up to 12 h in pH buffer 7.4. Interpolymer complexation was confirmed by FT-IR studies, compatibility of drug with excipients by DSC indicated no significant changes with drug. SEM studies revealed formation of round microspheres with pervious and uneven surface. In vitro release data from microspheres was analysed by kinetic model fitting for mechanism of drug release. Microspheres showed 5-10% of drug release in pH 1.2 which was further prevented by formulating coated tablets of microspheres using cellulose acetate phthalate. Conclusion: Targeted colon specific drug delivery of Budenoside with extended release up to 12 h was successfully achieved by formulation of tablets containing microspheres prepared by interpolymer complexation technique
Keywords: Budesonide; Colon Specific Delivery; Interpolymer Complexation; Microspheres; Cellulose Acetate phthalate